Repetition positivity following auditory intensity or frequency changes in young normal-hearing adults - Altın, Büşra; Colak, Hasan; Maskery, Charlie; Alter, Kai; Sedley, William (Frontiers in Neuroscience, 2026)
IntroductionGenerative mechanisms of perception such as predictive coding are used to explain how the brain perceives the world; such mechanisms are often experimentally probed using “deviant” stimuli that violate established patterns (including mismatch negativity), which also elicit responses related to lower-level processes such as stimulus-specific adaptation. However, little is still known about brain responses that indicate the strength of sensory predictions or reinforcement of sensory representations. Repetition positivity (RP) is a positive polarity evoked potential that gradually increases with each repetition of a stimulus, and is thought to reflect progressive strengthening of auditory sensory memory and/or habituation to repetitive stimuli. The aim of this study was to compare RP that follows a change in stimulus frequency with that following a change in stimulus intensity, the latter having not previously been studied.MethodsWe used roving sequences of isochronous 5 kHz pure tones (300 ms duration, 300ms inter-stimulus interval), which changed in frequency by 1 kHz (Experiment 1) or in intensity by 12 dB (Experiment 2) after every 30 stimuli. All changes were roving, such that an increase would be followed by a decrease, and vice versa.ResultsEvent-related potentials recorded with EEG indicated that frequency changes in either direction were followed by RP, whilst only intensity increases were followed by RP, and only a weak visual trend toward RP was apparent for intensity decreases. Observed RP was best explained by a logarithmic function over successive stimuli.ConclusionsRP robustly follows increases, but not necessarily decreases, in stimulus intensity, which appears smaller in amplitude than that elicited by similarly salient frequency changes, and reaches a plateau sooner. These observations offer insight into how intensity is processed similarly yet differently to other sensory attributes in an adaptive or predictive coding framework, and might have future utility in the study of clinical conditions related to aberrant predictive mechanisms.